Ta có công thức \(\frac{a}{b.c}=\frac{a}{c-b}.\left(\frac{1}{b}-\frac{1}{c}\right)\)
Dựa vào công thức trên, ta có
\(\frac{1}{1.2}=\frac{1}{2-1}.\left(1-\frac{1}{2}\right)\)
\(\frac{1}{2.3}=\frac{1}{3-2}.\left(\frac{1}{2}-\frac{1}{3}\right)\)
............................................
\(\frac{1}{49.50}=\frac{1}{50-49}.\left(\frac{1}{49}-\frac{1}{50}\right)\)
\(A=1.\left(1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+....+\frac{1}{49}-\frac{1}{50}\right)\)
\(\Rightarrow A=1-\frac{1}{50}=\frac{49}{50}\)
chắc chắn bạn ạ, ai thấy đúng hì ủng hộ nha
\(A=\frac{1}{1.2}+\frac{1}{2.3}+\frac{1}{3.4}+...+\frac{1}{49.50}=1-\frac{1}{50}=\frac{49}{50}\)\(\frac{49}{50}\)
A = \(\frac{1}{1\times2}+\frac{1}{2\times3}+...+\frac{1}{49\times50}\)
A = \(\frac{1}{1}-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+...+\frac{1}{49}-\frac{1}{50}\)
A = \(\frac{1}{1}-\frac{1}{50}\)
A = \(\frac{50}{50}-\frac{1}{50}\)
A = \(\frac{49}{50}\)
A=\(\frac{1}{1.2}+\frac{1}{2.3}+\frac{1}{3.4}+...+\frac{1}{49.50}\)
=\(\frac{1}{1}-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+...+\frac{1}{49}-\frac{1}{50}\)
\(=\frac{1}{1}-\frac{1}{50}\)
\(=\frac{50}{50}-\frac{1}{50}\)
\(=\frac{49}{50}\)
Vậy\(A=\frac{49}{50}\)